Research in Attacks, Intrusions, and Defenses 19th International Symposium, RAID 2016, Paris, France, September 19-21, 2016, Proceedings - Monrose, Fabian; Dacier, Marc; Blanc, Gregory; Garcia-Alfaro, Joaquin (Security and Cryptology, 2016)
This book constitutes the refereed proceedings oft he 19th International Symposium on Research in Attacks, Intrusions, and Defenses, RAID 2016, held in Evry, France, in September 2016. The 21 full papers presented were carefully reviewed and selected from 85 submissions. They are organized around the following topics: systems security; low-level attacks and defenses; measurement studies; malware analysis; network security; systematization of knowledge and experience reports; Web and mobile security.